PEMBELAJARAN MEMBACA PEMAHAMAN DENGAN STRATEGI THE COGNITIVE ACADEMIC LANGUAGE LEARNING APPROACH (CALLA) BERBASIS KEARIFAN LOKAL SISWA - Witri Annisa; Rio Rinaldi (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2017)
Abstract: The reading ability of Indonesian society is still low due to the low interest and reading habit. CALLA-based strategy of cognition by not forgetting aspects of metacognition can make students more precise in understanding a text in depth. Materials, media, and tests based on local wisdom are also expected to improve reading comprehension. This type of research is mixed methods with explanatory design. The sample of this research is taken with purposive purpose of two class, that is VII. 1 for the experimental class and VII.2 control class. The results of this study indicate that the implementation of CALLA strategy based on local wisdom in learning to read comprehension shows can increase student's interest to improve comprehension of reading. Similarly, the students' reading comprehension test results also show a significant improvement in the experimental class with CALLA strategies based on local wisdom. A significant level of effectiveness of reading comprehension learning with CALLA strategy based on local wisdom is 0.000 which means> α 0.05. That is, learning comprehension reading with CALLA strategy based on local wisdom is effective. The results of interviews and observations of teacher and student activities seen the influence of CALLA strategy based on local wisdom that makes students more enthusiastic and active in learning. Thus, CALLA strategy based on local wisdom is effective in improving students' reading comprehension skills. Abstrak: Kemampuan membaca masyarakat Indonesia masih rendah karena minat dan kebiasaan membaca yang rendah. Strategi CALLA berbasis kognisi tanpa melupakan aspek metakognisi dapat menjadikan siswa lebih tepat dalam memahami teks secara mendalam. Materi, media, dan tes yang diberikan berbasis kearifan lokal juga diharapkan dapat meningkatkan kemampuan membaca pemahaman. Penelitian ini memanfaatkan metode campuran dengan rancangan explanatory design. Sampel penelitian diambil dengan teknik purpose sampling dua kelas, yaitu VII.1 sebagai kelas eksperimen dan VII.2 sebagai kelas kontrol. Hasil penelitian menunjukkan bahwa penerapan stategi CALLA berbasis kearifan lokal dapat meningkatkan minat siswa untuk meningkatkan pemahaman. Hasil tes kemampuan membaca pemahaman siswa juga menunjukkan peningkatan yang signifikan pada kelas eksperimen. Tingkat signifikan keefektifan pembelajaran membaca pemahaman dengan strategi CALLA berbasis kearifan lokal mencapai 0,000 yang berarti > α 0,05. Artinya, pembelajaran membaca pemahaman dengan strategi CALLA berbasis kearifan lokal efektif. Hasil wawancara dan observasi aktivitas guru dan siswa pun menunjukkan bahwa metode ini membuat siswa lebih antusias dan aktif dalam pembelajaran. Permalink/DOI: http://dx.doi.org/10.15408/dialektika.v4i2.6152.